Karakter Aşınması Ölçeğinin Geliştirilmesi: Geçerlik ve Güvenilirlik Çalışması - (:unkn) unknown (My University, 2019)
Bu çalışmanın amacı, araştırma görevlilerinin “Karakter Aşınması” düzeylerini belirlemeye yarayan bir ölçek geliştirmektir. Ölçeğin geliştirilme sürecinde, taslak form oluşturularak uzman görüşüne sunulmuştur. Lawshe analizi ile yapılan kapsam geçerliği süreçleri sonucunda, taslak formdan yedi madde atılıp, dört madde eklenmiştir. Oluşturulan 50 maddelik taslak form İstanbul’da bulunan vakıf ve devlet üniversitelerinde çalışan 312 araştırma görevlisine uygulanarak, elde edilen veriler analiz edilmiştir. KMO değerinin .88 olduğu ve veri setinin faktörlenmeye uygun olduğu gözlenmiştir. Karakter Aşınması Ölçeği’nin, özdeğeri 1.00’in üzerinde olan dört faktörlü yapı sergilediği görülmüştür. Bu dört faktör aidiyet, güvencesizlik, sürüklenme ve bireysellik olarak isimlendirilmiştir. Ölçeğin tamamı için bulunan Cronbach alfa değeri .90’dır. Doğrulayıcı faktör analizi sonucunda dört boyutlu modelin kabul edilebilir uyum verdiği görülmüştür (x2/df=2.6, RMSEA=.06, GFI=.90, CFI=.92, TLI=.91). Çalışma sonucunda elde edilen bulgular doğrultusunda, geliştirilen Karakter Aşınması Ölçeği’nin geçerli ve güvenilir bir ölçme aracı olduğu söylenebilir

The aim of this study is to develop a scale that determines the “Corrosion of Character” levels of research assistants. In the development process of the scale draft was presented to the evaluation of expert views. After the scope validity processes held via Lawshe analysis, seven items were taken out of the scale and four items were added. Totally 312 research assistants working at different private and state universities in Istanbul were subjected to the draft scale, which was comprised of 50 items in the 2018-2019 academic year. In the light of the data analysis, it was observed that the KMO value was .88 and the data set was suitable for the factorization. In order to detect the structural validity of the scale, Principle Components and Exploratory Factor Analysis (EFA) were conducted and in the end “Corrosion of Character Scale” showed a four-factored (belongingness, precarity, scud, individuality) structure with an eigenvalue of over 1.00, and Cronbach’s alpha (.90) coefficients for the totality of the scale were observed. As a result of the Confirmatory Factor Analysis (CFA) applied, the fit indices were found as an acceptable level (x2/df=2.6, RMSEA=.06, GFI=.90, CFI=.92, TLI=.91). The results obtained prove that the “Corrosion of Character Scale” as a measurement tool is valid and reliable.
The Corrosion of Character Scale Development: A Validity and Reliability Study